Photosensitive resin composition, photosensitive dry film, printed wiring board

CN122945334APending Publication Date: 2026-10-20HANGZHOU FIRST ELECTRONIC MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611168362.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]鉴于背景技术中存在的技术问题,本发明提供了一种感光树脂组合物、感光干膜及印刷线路板,以解决现有感光树脂组合物难以在保证LDI曝光速度、解析、附着和耐电镀性能的同时,减少VCP图形电镀过程中电镀铜分层的问题

Benefits of technology

[0026]应用本发明的技术方案,通过碱溶性树脂、光聚合单体和光引发剂的配合,使感光树脂组合物具备形成抗蚀剂图形所需的成膜、碱显影和光固化基础;并通过将感光树脂组合物在385nm处的单位厚度吸光度控制在0.005~0.030,使感光层能够与LDI曝光光源相匹配,避免因吸光不足导致曝光效率低、固化不充分或显影残留,也避免因吸光过强导致表层固化过快、底部或界面区域固化不足,从而形成固化程度适宜、解析良好且显影洁净的抗蚀剂图形。同时,通过采用由含羧基的不饱和单体和丙烯酸酯类单体共聚得到的碱溶性树脂,相较于含有苯乙烯类结构单元的树脂体系,能够在保证碱显影性和成膜强度的基础上,改善感光层的柔韧性、铜面附着稳定性和边缘密封可靠性。由此,本发明并非单纯提高感光层的曝光灵敏度,而是通过385nm单位厚度吸光度与非苯乙烯类碱溶性树脂体系的协同控制,使感光层在LDI曝光后的固化状态、显影开口洁净性和铜面附着稳定性共同得到改善,从而提高其对VCP图形电镀工艺的适应性,减少电镀铜分层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention provides a photosensitive resin composition, a photosensitive dry film, and a printed circuit board, relating to the field of polymer technology. The photosensitive resin composition comprises an alkali-soluble resin, a photopolymerizable monomer, and a photoinitiator; the absorbance per unit thickness of the photosensitive resin composition under ultraviolet light at a wavelength of 385 nm is 0.005~0.030; wherein, the absorbance per unit thickness refers to the absorbance of a coating formed by the photosensitive resin composition with a thickness of 1 μm; the alkali-soluble resin is obtained by copolymerizing a carboxyl-containing unsaturated monomer and an acrylate monomer. The technical solution of this invention can effectively solve the problem that existing photosensitive resin compositions are unable to reduce copper delamination during VCP pattern electroplating while ensuring LDI exposure speed, resolution, adhesion, and electroplating resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer technology, and more specifically, to a photosensitive resin composition, a photosensitive dry film, and a printed circuit board. Background Technology

[0002] Currently, photosensitive resin compositions are widely used in pattern transfer processes for electronic devices such as printed circuit boards (PCBs). As PCBs become increasingly dense and feature finer lines, traditional mask exposure methods are gradually failing to meet requirements in terms of pattern accuracy, production flexibility, and process efficiency. Laser direct imaging (LDI), which eliminates the need for masks and allows direct exposure based on digital patterns, offers advantages such as high pattern accuracy, flexible production switching, and suitability for fine line processing, thus gaining increasing application in PCB manufacturing.

[0003] However, LDI exposure places higher demands on the photoresist composition's photoresist properties. The absorption state of the photoresist composition at the LDI exposure wavelength affects the exposure speed, curing degree, and thickness-direction curing uniformity of the photosensitive layer. Insufficient light absorption can easily lead to low exposure efficiency or incomplete curing; excessive light absorption may cause the surface layer to cure too quickly while the bottom layer is insufficiently cured, thus affecting the resolution, adhesion, and electroplating resistance of the resist pattern. Especially in subsequent pattern electroplating processes, the curing state and adhesion stability of the resist pattern further affect the bonding reliability of the electroplated copper layer in the development opening area.

[0004] Meanwhile, the application of vertical continuous plating (VCP) is gradually increasing in pattern plating processes. VCP plating has the advantages of high continuity, high production efficiency, and good coating uniformity, and is especially suitable for processing fine lines and high aspect ratio holes. However, the online degreasing and micro-etching pretreatment time for VCP plating is relatively short, and the surface treatment effect is prone to being insufficient. In this case, if the resist pattern formed by the photosensitive resin composition cannot simultaneously ensure sufficient curing, adhesion stability, and electroplating resistance, the subsequent copper plating layer may not bond well with the original copper surface, resulting in copper plating delamination. Summary of the Invention

[0005] In view of the technical problems existing in the background art, the present invention provides a photosensitive resin composition, a photosensitive dry film and a printed circuit board, so as to solve the problem that existing photosensitive resin compositions are difficult to reduce copper delamination during VCP pattern electroplating while ensuring LDI exposure speed, resolution, adhesion and electroplating resistance.

[0006] To address the aforementioned problems, according to a first aspect of the present invention, a photosensitive resin composition is provided, comprising an alkali-soluble resin, a photopolymerizable monomer, and a photoinitiator; the photosensitive resin composition has an absorbance per unit thickness of 0.005 to 0.030 under ultraviolet light at a wavelength of 385 nm; wherein the absorbance per unit thickness is the absorbance of a coating formed by the photosensitive resin composition with a thickness of 1 μm; the alkali-soluble resin is obtained by copolymerization of a carboxyl-containing unsaturated monomer and an acrylate monomer.

[0007] Furthermore, the absorbance per unit thickness of the photosensitive resin composition under ultraviolet light at a wavelength of 385 nm is 0.008~0.022.

[0008] Furthermore, the carboxyl-containing unsaturated monomers include at least one of acrylic acid, methacrylic acid, butenoic acid, maleic acid, maleic anhydride, and itaconic acid.

[0009] Furthermore, the acrylate monomers include at least one of methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, amyl methacrylate, hexyl methacrylate, lauryl methacrylate, octadecyl methacrylate, hydroxymethyl methacrylate, hydroxyethyl methacrylate, ethyl N,N-dimethyl (meth)acrylate, ethyl N,N-diethyl (meth)acrylate, propyl N,N-dimethyl (meth)acrylate, and propyl N,N-diethyl (meth)acrylate.

[0010] Furthermore, the carboxyl-containing unsaturated monomers include at least one of acrylic acid and methacrylic acid; the acrylate monomers include at least one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, and cyclohexyl methacrylate.

[0011] More preferably, the alkali-soluble resin is obtained by copolymerization of methacrylic acid, methyl methacrylate and butyl methacrylate.

[0012] Furthermore, the mass ratio of methacrylic acid to methyl methacrylate is (20~30):(45~55); the mass ratio of methyl methacrylate to butyl methacrylate is (45~55):(20~30); and the mass ratio of methacrylic acid to butyl methacrylate is (20~30):(20~30).

[0013] Further, based on parts by weight, the photosensitive resin composition comprises: 40-70 parts by weight of alkali-soluble resin, 20-50 parts by weight of photopolymerizable monomer, and 3-10 parts by weight of photoinitiator.

[0014] Further, the photoinitiator includes at least one of 2,4,5-triarylimidazolium dimer compounds, ketone photoinitiators, N-phenylglycine, acridine compounds, and coumarin compounds; wherein the 2,4,5-triarylimidazolium dimer compounds include 2,2'-di(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-diimidazole, (2,2',4-tris(2-chlorophenyl)-5-(3,4-dimethoxyphenyl)-4',5'-diphenyl-1,1'- At least one of the following: (diimidazole); ketone photoinitiators including at least one of 4,4'-bis(diethylamino)benzophenone, 4,4'-bis(dimethylamino)benzophenone, and 4,4'-dimethoxybenzophenone; acridine compounds including at least one of 9-phenylacridine, 9-(p-methylphenyl)acridine, and 9-(m-methylphenyl)acridine; and coumarin compounds including at least one of 7-diethylamino-4-methylcoumarin, 3-phenyl-7-aminocoumarin, and 3-heterocyclic-7-aminocoumarin.

[0015] Furthermore, the photopolymerizable monomers include at least one of the following: nonylphenol acrylate, ethoxylated nonylphenol acrylate, ethoxylated propionylphenol acrylate, ethoxylated propionyl dimethacrylate, bisphenol A dimethacrylate, ethoxylated bisphenol A dimethacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propionyl trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, di-trimethylolpropane tetraacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate.

[0016] More preferably, the photoinitiator includes 2,4,5-triarylimidazolium dimer compounds, ketone photoinitiators, and N-phenylglycine.

[0017] Furthermore, the mass ratio of 2,4,5-triarylimidazolium dimer compounds, ketone photoinitiators, and N-phenylglycine is (3.0~4.0):(0.05~0.4):(0.01~0.04).

[0018] Further, based on parts by weight, the photosensitive resin composition further includes: 0.2 to 5.0 parts by weight of additives and 100 to 200 parts by weight of solvent; wherein the additives include at least one of adhesion promoters, plasticizers, dyes, fillers, flame retardants, stabilizers, leveling agents, peel promoters, antioxidants, fragrances, imaging agents, and thermal crosslinking agents.

[0019] Furthermore, the weight-average molecular weight of the alkali-soluble resin is 50,000 g / mol to 150,000 g / mol.

[0020] More preferably, the weight-average molecular weight of the alkali-soluble resin is 80,000 g / mol to 120,000 g / mol.

[0021] Furthermore, the acid value of the alkali-soluble resin is 100mgKOH / g~200mgKOH / g.

[0022] More preferably, the acid value of the alkali-soluble resin is 120 mg KOH / g to 200 mg KOH / g.

[0023] According to a second aspect of the present invention, a photosensitive dry film is provided, comprising a support layer, a photosensitive layer and a protective layer disposed sequentially; wherein the photosensitive layer is formed by coating and drying the above-mentioned photosensitive resin composition.

[0024] Furthermore, the thickness of the photosensitive layer is 20μm~50μm.

[0025] According to a third aspect of the present invention, a printed circuit board is provided, wherein the above-mentioned photosensitive dry film is used in the preparation process of the printed circuit board, and the preparation process of the printed circuit board includes LDI exposure, development and VCP pattern electroplating treatment.

[0026] By applying the technical solution of this invention, the photosensitive resin composition possesses the necessary film-forming, alkali-developing, and photocuring capabilities for forming resist patterns through the combination of alkali-soluble resin, photopolymerizable monomers, and photoinitiators. Furthermore, by controlling the absorbance per unit thickness of the photosensitive resin composition at 385 nm to 0.005~0.030, the photosensitive layer can be matched with the LDI exposure light source, avoiding low exposure efficiency, incomplete curing, or development residue due to insufficient light absorption, and also avoiding excessively rapid surface curing and insufficient curing in the bottom or interface areas due to excessive light absorption. This results in a resist pattern with suitable curing degree, good resolution, and clean development. Simultaneously, by using an alkali-soluble resin obtained by copolymerizing carboxyl-containing unsaturated monomers and acrylate monomers, compared to resin systems containing styrene structural units, the flexibility of the photosensitive layer, copper surface adhesion stability, and edge sealing reliability can be improved while ensuring alkali developability and film strength. Therefore, this invention does not simply improve the exposure sensitivity of the photosensitive layer, but rather improves the curing state, development opening cleanliness, and copper surface adhesion stability of the photosensitive layer after LDI exposure through the synergistic control of absorbance per unit thickness of 385nm and non-styrene alkali-soluble resin system. This enhances its adaptability to VCP pattern electroplating process and reduces copper plating delamination. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0028] As described in the background section of this invention, existing photosensitive resin compositions struggle to reduce copper delamination during VCP pattern electroplating while ensuring LDI exposure speed, resolution, adhesion, and electroplating resistance. To address this issue, in a typical embodiment of this invention, a photosensitive resin composition is provided, comprising an alkali-soluble resin, a photopolymerizable monomer, and a photoinitiator; the photosensitive resin composition exhibits an absorbance of 0.005~0.030 per unit thickness under ultraviolet light at a wavelength of 385 nm; wherein the absorbance per unit thickness refers to the absorbance of a coating formed by the photosensitive resin composition with a thickness of 1 μm; the alkali-soluble resin is obtained by copolymerizing a carboxyl-containing unsaturated monomer and an acrylate monomer.

[0029] The photosensitive resin composition of this invention is mainly applicable to pattern transfer materials for printed circuit boards, especially photosensitive dry film systems that require LDI exposure imaging and VCP pattern electroplating. In this application scenario, LDI exposure is used to form a photocurable area of ​​the photosensitive layer according to a preset circuit pattern, and a resist pattern is obtained after development. This resist pattern not only needs to have good resolution and adhesion properties, but also needs to maintain stable edge blocking effect and resistance to electroplating solution impact during the subsequent VCP pattern electroplating process. Since the online degreasing and micro-etching pretreatment time for VCP pattern electroplating is relatively short, it has higher requirements for the cleanliness of the development opening area, the adhesion stability of the resist pattern to the copper surface, and the reliability of electroplating resistance. If the exposure curing state or interface stability of the photosensitive layer is insufficient, it is easy to cause the electroplated copper layer to not bond firmly to the original copper surface, resulting in copper plating delamination. Therefore, by controlling the absorbance per unit thickness of the photosensitive resin composition at a wavelength of 385 nm and using an alkali-soluble resin obtained by copolymerizing carboxyl-containing unsaturated monomers and acrylate monomers, the present invention helps to form a resist pattern with appropriate curing degree, clean development and stable adhesion after LDI exposure of the photosensitive layer. This reduces the risk of copper delamination during VCP pattern electroplating while taking into account exposure speed, resolution, adhesion and electroplating resistance.

[0030] Specifically, the photosensitive resin composition of the present invention comprises an alkali-soluble resin, a photopolymerizable monomer, and a photoinitiator. The alkali-soluble resin, as the main film-forming and binding component of the photosensitive layer, enables the photosensitive layer to possess suitable alkali developability, allowing insufficiently exposed and cured areas to be removed during development. It also influences the adhesion stability of the photosensitive layer to the copper surface, the film flexibility, and the resistance to electroplating solution impact. The photopolymerizable monomer participates in the photopolymerization reaction after exposure, increasing the degree of cross-linking and curing in the exposed area, thereby enhancing the mechanical strength, edge integrity, and developability and electroplating resistance of the resist pattern. The photoinitiator absorbs the energy of the exposure light source and initiates the photopolymerization reaction; its type and amount affect the photosensitive layer's responsiveness to LDI exposure wavelengths, exposure speed, and thickness-direction curing state. The combination of these components enables the photosensitive resin composition to form a resist pattern with good resolution, adhesion, and electroplating resistance under LDI exposure.

[0031] In this invention, the absorbance per unit thickness is used to characterize the absorption capacity of the photosensitive resin composition for 385nm wavelength light after forming a photosensitive layer. This absorbance per unit thickness refers to the absorbance of the photosensitive layer at 385nm after coating and drying the photosensitive resin composition to form a photosensitive layer of a certain thickness, and then calculating the absorbance per 1μm of thickness according to the thickness of the photosensitive layer. Specifically, the photosensitive resin composition can be coated onto a support film and dried to form a photosensitive layer. During testing, the protective film is removed, and the support film is used as the background sample. The absorbance A385 of the photosensitive layer at 385nm is measured using a UV-Vis spectrophotometer, and the absorbance per unit thickness T is calculated based on the thickness of the photosensitive layer, i.e., absorbance per unit thickness = A385 / T, where the unit of T is μm. For example, when the thickness of the photosensitive layer is 40 μm and the A385 is 0.32, its absorbance per unit thickness is 0.008; when the thickness of the photosensitive layer is 40 μm and the A385 is 0.88, its absorbance per unit thickness is 0.022.

[0032] Controlling the absorbance per unit thickness of the photosensitive resin composition at 385nm to 0.005~0.030 helps to match the photosensitive layer with the LDI exposure light source. If the absorbance per unit thickness is too low, it indicates that the photosensitive layer does not absorb enough light from the 385nm exposure light source, which can easily lead to reduced exposure efficiency, increased exposure energy requirements, insufficient curing, or residue in the opening area after development. This residue will affect the cleanliness of the original copper surface in the opening area. Since the online degreasing and micro-etching time of VCP pattern electroplating is relatively short, it is more sensitive to the cleanliness and activation state of the opening copper surface, which can easily lead to poor adhesion between the subsequent electroplated copper layer and the original copper surface. If the absorbance per unit thickness is too high, the incident light is easily concentrated on the surface of the photosensitive layer and absorbed, resulting in insufficient curing at the bottom of the photosensitive layer or in the area near the copper surface. This will affect the adhesion stability of the resist pattern to the copper surface and the sealing of the pattern edge. Under the action of VCP electroplating solution jetting, electroplating solution wetting, and electroplating stress, the edges of the resist pattern are more prone to electroplating solution penetration or seepage, which can induce delamination of the electroplated copper. Specifically, the absorbance per unit thickness of the photosensitive resin composition at 385 nm can be in the range of 0.005, 0.010, 0.015, 0.020, 0.025, 0.030, or any combination thereof.

[0033] Meanwhile, the alkali-soluble resin in this invention is obtained by copolymerizing carboxyl-containing unsaturated monomers and acrylate monomers. The carboxyl-containing unsaturated monomers impart suitable alkali developability to the resin and help improve the interfacial interaction between the photosensitive layer and the copper surface; the acrylate monomers improve the resin's film-forming properties, flexibility, and adhesion stability. The combination of these two components helps to form a cleaner opening area in the photosensitive layer after exposure and development, and ensures that the resist pattern maintains good edge stability and resistance to plating bath impact during subsequent VCP pattern electroplating.

[0034] Compared to alkali-soluble resins containing styrene or styrene derivative structural units, the aromatic rigid structure in styrene-based structural units tends to improve film hardness and hydrophobicity, but may also cause the photosensitive layer to become brittle and reduce the film's adaptability to the microstructure of the copper surface and its interfacial adhesion stability. Under the short pretreatment time, electroplating solution spraying, and electroplating stress of VCP pattern electroplating, the aforementioned problem of insufficient interfacial adaptability is more likely to manifest as micro-gaps at the edges of the resist pattern, electroplating solution penetration or seepage, thereby inducing copper delamination. This invention uses an alkali-soluble resin obtained by copolymerizing carboxyl-containing unsaturated monomers and acrylate monomers, which helps to improve the flexibility of the photosensitive layer, the adhesion stability of the copper surface, and the reliability of edge sealing while ensuring alkali developability and film strength, thereby reducing the risk of copper delamination during VCP pattern electroplating.

[0035] Therefore, this invention, through the combination of alkali-soluble resin, photopolymerizable monomers, and photoinitiators, enables the photosensitive resin composition to possess the necessary film-forming, alkali-developing, and photocuring foundations for forming resist patterns. Furthermore, by controlling the absorbance per unit thickness of the photosensitive resin composition at 385 nm to 0.005~0.030, the photosensitive layer can be matched with the LDI exposure light source, avoiding low exposure efficiency, incomplete curing, or development residue due to insufficient light absorption, and also avoiding excessively strong light absorption leading to overly rapid surface curing and insufficient curing in the bottom or interface areas. This results in a resist pattern with suitable curing degree, good resolution, and clean development. Simultaneously, by using an alkali-soluble resin obtained by copolymerizing carboxyl-containing unsaturated monomers and acrylate monomers, compared to resin systems containing styrene structural units, it can improve the flexibility of the photosensitive layer, the adhesion stability to copper surfaces, and the reliability of edge sealing while ensuring alkali developability and film strength. Therefore, this invention does not simply improve the exposure sensitivity of the photosensitive layer, but rather improves the curing state, development opening cleanliness, and copper surface adhesion stability of the photosensitive layer after LDI exposure through the synergistic control of absorbance per unit thickness of 385nm and non-styrene alkali-soluble resin system. This enhances its adaptability to VCP pattern electroplating process and reduces copper plating delamination.

[0036] In some embodiments, the absorbance per unit thickness of the photosensitive resin composition under ultraviolet light at a wavelength of 385 nm is 0.008 to 0.022. Further controlling the absorbance per unit thickness of the photosensitive resin composition at 385 nm to be 0.008 to 0.022 helps to further optimize the absorption state of the photosensitive layer to the LDI exposure light source. This range helps to reduce problems such as low exposure efficiency, insufficient curing, or increased development residue when the absorbance per unit thickness is too low. It also helps to reduce problems such as strong light absorption on the surface of the photosensitive layer and insufficient curing in the bottom or near the copper surface when the absorbance per unit thickness is too high. This helps to further improve the resolution performance, adhesion stability, and electroplating reliability of the resist pattern, and reduces the risk of copper delamination during VCP pattern electroplating. Specifically, the absorbance per unit thickness of the photosensitive resin composition at 385 nm can be a range of 0.008, 0.010, 0.015, 0.020, 0.022, or any combination thereof.

[0037] In some embodiments, the carboxyl-containing unsaturated monomers include at least one selected from acrylic acid, methacrylic acid, butenoic acid, maleic acid, maleic anhydride, and itaconic acid. By controlling the type of carboxyl-containing unsaturated monomers, these monomers help introduce carboxyl structures into alkali-soluble resins, thereby improving the resin's alkali-developability and making it easier to remove underexposed and cured areas during development. Simultaneously, the carboxyl structure also helps enhance the interfacial interaction between the photosensitive layer and the copper surface, thereby improving the cleanliness of the development opening and the adhesion stability of the resist pattern.

[0038] In some embodiments, the acrylate monomers include at least one selected from methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, amyl methacrylate, hexyl methacrylate, lauryl methacrylate, octadecyl methacrylate, methyl methacrylate, hydroxyethyl methacrylate, ethyl N,N-dimethyl (meth)acrylate, ethyl N,N-diethyl (meth)acrylate, propyl N,N-dimethyl (meth)acrylate, and propyl N,N-diethyl (meth)acrylate. By controlling the selectable types of acrylate monomers, it is helpful to adjust the film-forming properties, flexibility, polarity, and adhesion properties of the alkali-soluble resin. Among them, (meth)acrylate monomers with shorter alkyl chains help improve the film-forming strength and resist pattern retention of the resin; (meth)acrylate monomers with longer alkyl chains help improve the film flexibility and adhesion to the microstructure of the copper surface; (meth)acrylate monomers containing hydroxyl groups help improve the resin polarity and interfacial interaction, thereby improving the adhesion stability between the photosensitive layer and the copper surface; (meth)acrylate monomers containing tertiary amine structures help adjust the resin polarity and development adaptability. Through the selection and combination of the above monomers, a better balance can be achieved between alkali-soluble resins in terms of film-forming strength, flexibility, alkali developability, and copper surface adhesion stability, thereby further improving the development cleanliness of the photosensitive layer, the edge stability of the resist pattern, and the electroplating reliability in the subsequent VCP pattern electroplating process.

[0039] It should be noted that in this invention, "(meth)acrylate" refers to acrylate and / or methacrylate, for example, "(meth)acrylate" refers to methyl acrylate and / or methyl methacrylate, and "(meth)acrylate" refers to butyl acrylate and / or butyl methacrylate.

[0040] In some embodiments, the carboxyl-containing unsaturated monomers include at least one of acrylic acid and methacrylic acid; the acrylate monomers include at least one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, and cyclohexyl methacrylate. Further control over the types of carboxyl-containing unsaturated monomers and acrylate monomers helps to further improve the controllability of the alkali-soluble resin composition. Specifically, acrylic acid or methacrylic acid helps to improve alkali developability and copper interface interaction; methyl methacrylate and ethyl methacrylate help to improve film strength and pattern retention; butyl methacrylate and 2-ethylhexyl methacrylate help to improve film flexibility and adhesion stability; and cyclohexyl methacrylate helps to improve film chemical resistance and pattern stability. The combination of these monomers helps to further balance developability, film strength, flexibility, and electroplating resistance.

[0041] In some preferred embodiments, the alkali-soluble resin is obtained by copolymerizing methacrylic acid, methyl methacrylate, and butyl methacrylate. Controlling the composition of the alkali-soluble resin by copolymerizing methacrylic acid, methyl methacrylate, and butyl methacrylate helps to further optimize the alkali developability, film strength, flexibility, and copper surface adhesion stability of the alkali-soluble resin. Methacrylic acid contains carboxyl groups, which helps to give the alkali-soluble resin suitable alkali developability, making it easier to remove insufficiently exposed and cured areas during development, and also helps to improve the interfacial interaction between the photosensitive layer and the copper surface. Methyl methacrylate has a relatively high glass transition temperature and good film-forming support, which helps to improve the film strength, pattern retention, and development impact resistance of the photosensitive layer. Butyl methacrylate has relatively flexible alkyl segments, which helps to improve the film flexibility and adaptability to the microstructure of the copper surface, thereby improving the adhesion stability of the resist pattern to the copper surface. When these three components are combined, it helps to avoid problems such as insufficient chemical resistance of the film due to emphasizing only the developability, increased tendency to harden and become brittle due to emphasizing only the strength of the film, or decreased pattern retention due to emphasizing only the flexibility. This results in better overall stability of the photosensitive layer during LDI exposure, development, and subsequent VCP pattern electroplating.

[0042] In some embodiments, the mass ratio of methacrylic acid to methyl methacrylate is (20-30):(45-55); the mass ratio of methyl methacrylate to butyl methacrylate is (45-55):(20-30); and the mass ratio of methacrylic acid to butyl methacrylate is (20-30):(20-30). Controlling the proportions of methacrylic acid, methyl methacrylate, and butyl methacrylate within appropriate ranges helps to further coordinate the interaction between the three structural units. When the proportion of methacrylic acid is appropriate, it helps to ensure that the resin has sufficient alkaline developability and copper interface interaction, reducing the risk of incomplete development or residue in open areas. If its proportion is too low, it may be detrimental to development removal and interface interaction; if its proportion is too high, it may make the film layer too alkali-loving, affecting the developability and electroplating stability of the resist pattern. When the proportion of methyl methacrylate (MMA) is appropriate, it helps improve the film strength of the photosensitive layer and the ability to retain patterns after exposure. If the proportion is too low, the film support may be insufficient; if the proportion is too high, the film hardness will increase, which may be detrimental to bonding adaptability and edge sealing reliability. When the proportion of butyl methacrylate (BMA) is appropriate, it helps improve the flexibility of the film and the adhesion stability to the copper surface. If the proportion is too low, the film is prone to being too hard; if the proportion is too high, it may affect the pattern strength and electroplating resistance.

[0043] Through the aforementioned ternary copolymer structure and its proportion control, the alkali-soluble resin can achieve a good balance between alkali developability, film strength, and flexibility. This allows the photosensitive layer to maintain its pattern well after exposure while also forming a clean opening area during development. Simultaneously, it improves the adhesion stability of the resist pattern to the copper surface and the reliability of edge sealing. This helps to further reduce the risk of plating solution penetration, seepage, and copper delamination during VCP pattern electroplating due to development residue, film hardening and embrittlement, edge micro-gaps, or insufficient copper surface adhesion. Specifically, the mass ratio of methacrylic acid, methyl methacrylate, and butyl methacrylate can be 20:45:20, 20:50:25, 25:50:25, 30:50:25, 30:55:30, or any combination thereof.

[0044] In some embodiments, the photosensitive resin composition comprises, by weight, 40-70 parts of alkali-soluble resin, 20-50 parts of photopolymerizable monomer, and 3-10 parts of photoinitiator. Controlling the weight percentages of each component in the photosensitive resin composition helps to harmonize the film-forming properties, developability, and exposure-curing capabilities of the composition. When the alkali-soluble resin content is within the above range, it helps to improve film continuity, adhesion stability, and development control; when the photopolymerizable monomer content is within the above range, it helps to improve the degree of cross-linking curing and pattern intensity in the exposed area; when the photoinitiator content is within the above range, it helps to improve exposure reaction efficiency and curing depth. The combination of these three components helps to further improve the resolution, adhesion, and electroplating resistance of the resist pattern.

[0045] In some embodiments, the photoinitiator includes at least one selected from 2,4,5-triarylimidazolium dimers, ketone photoinitiators, N-phenylglycine, acridine compounds, and coumarin compounds; wherein the 2,4,5-triarylimidazolium dimer includes 2,2'-di(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-diimidazole, (2,2',4-tris(2-chlorophenyl)-5-(3,4-dimethoxyphenyl)-4',5'-diphenyl-1,1 The photoinitiator comprises at least one of the following: 4,4'-diimidazole; ketone photoinitiators include at least one of 4,4'-bis(diethylamino)benzophenone, 4,4'-bis(dimethylamino)benzophenone, and 4,4'-dimethoxybenzophenone; acridine compounds include at least one of 9-phenylacridine, 9-(p-methylphenyl)acridine, and 9-(m-methylphenyl)acridine; and coumarin compounds include at least one of 7-diethylamino-4-methylcoumarin, 3-phenyl-7-aminocoumarin, and 3-heterocyclic-7-aminocoumarin. By controlling the specific type of photoinitiator, the responsiveness of the photosensitive resin composition to LDI exposure light sources can be improved. Specifically, 2,4,5-triarylimidazolium dimers contribute to providing basic free radical initiation capabilities; ketone photoinitiators enhance the system's response to near-ultraviolet light; and acridine and coumarin compounds help regulate the system's light absorption and sensitizing effect. The combination of the above photoinitiators helps to achieve a more suitable exposure speed and curing degree for the photosensitive layer under LDI exposure conditions.

[0046] In some embodiments, the photopolymerizable monomers include at least one of nonylphenol acrylate, ethoxylated nonylphenol acrylate, ethoxylated propionoxylated nonylphenol acrylate, ethoxylated propionoxylated dimethacrylate, bisphenol A dimethacrylate, ethoxylated bisphenol A dimethacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propionoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, di-trimethylolpropane tetraacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate. By controlling the specific type of photopolymerizable monomer, it is helpful to adjust the crosslinking density, film strength, and flexibility of the photosensitive layer after exposure. Photopolymerizable monomers with different functionalities and structures can adjust the hardness, chemical resistance, edge retention ability, and adhesion stability of the cured film, thereby helping to further improve the stability of the resist pattern during development and VCP pattern electroplating processes.

[0047] In some preferred embodiments, the photoinitiator includes 2,4,5-triarylimidazolium dimers, ketone photoinitiators, and N-phenylglycine. By further controlling the preferred types of photoinitiators, 2,4,5-triarylimidazolium dimers help provide basic free radical initiation capabilities, enabling the photopolymerizable monomers to polymerize and cure under exposure conditions; ketone photoinitiators help improve the system's responsiveness to near-ultraviolet light sources, improving the exposure speed and curing efficiency of the photosensitive layer; and N-phenylglycine helps improve the exposure speed and curing efficiency, thereby further adjusting the photoresponse capability, initiation efficiency, and thickness-direction curing state of the photoinitiation system. The combination of these photoinitiators helps the photosensitive layer achieve a more suitable exposure speed and curing degree under LDI exposure conditions, and further improves the resolution, edge stability, and electroplating reliability of the resist pattern.

[0048] In some embodiments, the mass ratio of 2,4,5-triarylimidazolium dimer, ketone photoinitiator, and N-phenylglycine is (3.0~4.0):(0.05~0.4):(0.01~0.04). Controlling this mass ratio helps to further balance the basic initiation capability and near-UV response capability of the photoinitiation system. Specifically, an appropriate content of the 2,4,5-triarylimidazolium dimer helps ensure sufficient photopolymerization; an appropriate content of the ketone photoinitiator helps to improve exposure response efficiency and reduce problems such as insufficient sensitization or excessively rapid surface curing; and an appropriate content of N-phenylglycine helps to improve exposure speed and curing efficiency. Through the above-mentioned ratio control, the exposure latitude, thickness-direction curing uniformity, and pattern stability of the photosensitive layer can be further improved. Specifically, the mass ratio of 2,4,5-triarylimidazolium dimer compounds, ketone photoinitiators, and N-phenylglycine can be 3:0.05:0.01, 3:0.4:0.04, 3:0.05:0.04, 3.5:0.2:0.03, 4:0.4:0.01, 4:0.4:0.04, 4:0.05:0.01, or any combination thereof.

[0049] In some preferred embodiments, the photosensitive resin composition further includes, by weight, 0.2 to 5.0 parts of additives and 100 to 200 parts of solvent; the present invention does not limit the specific type of additives, which can be selected according to actual needs. For example, the additives include at least one of adhesion promoters, plasticizers, dyes, fillers, flame retardants, stabilizers, leveling agents, peel accelerators, antioxidants, fragrances, imaging agents, and thermal crosslinking agents. Specifically, the addition of solvents helps to promote thorough mixing between the components of the photosensitive resin composition, and the solvents can be those conventionally used in the art, preferably butanone and ethanol. The dyes can be malachite green, brilliant green, leuco crystal violet, etc.

[0050] In some embodiments, the weight-average molecular weight of the alkali-soluble resin is 50,000 g / mol to 150,000 g / mol; the acid value of the alkali-soluble resin is 100 mg KOH / g to 200 mg KOH / g. By controlling the weight-average molecular weight and acid value of the alkali-soluble resin, it is helpful to balance the film-forming strength, developing performance, and adhesion stability of the alkali-soluble resin. When the weight-average molecular weight is within the above range, it helps to reduce the problems of insufficient mechanical strength of the film layer and weak resistance to electroplating solution impact. It also helps to reduce the problems of difficult development and removal or development residue caused by excessively high weight-average molecular weight. When the acid value is within the above range, it helps to give the photosensitive layer suitable alkali developability, reduce the problem of insufficient development caused by excessively low acid value, and also help to reduce the problem of decreased resistance to developing solution and electroplating solution caused by excessively high acid value. This further improves the developing cleanliness, pattern retention, and stability of the photosensitive layer during VCP pattern electroplating. Specifically, the weight-average molecular weight of the alkali-soluble resin can be in the range of 50,000 g / mol, 60,000 g / mol, 80,000 g / mol, 100,000 g / mol, 120,000 g / mol, 150,000 g / mol, or any combination thereof; the acid value of the alkali-soluble resin can be in the range of 100 mg KOH / g, 120 mg KOH / g, 140 mg KOH / g, 160 mg KOH / g, 180 mg KOH / g, 200 mg KOH / g, or any combination thereof.

[0051] In some preferred embodiments, the weight-average molecular weight of the alkali-soluble resin is 80,000 g / mol to 120,000 g / mol; the acid value of the alkali-soluble resin is 120 mg KOH / g to 200 mg KOH / g. Controlling the weight-average molecular weight to 80,000 g / mol to 120,000 g / mol helps the alkali-soluble resin to further improve film-forming strength and molecular chain entanglement, while further avoiding the impact of excessively high molecular weight on development and removal. Controlling the acid value to 120 mg KOH / g to 200 mg KOH / g helps to further improve the alkali development adaptability of the photosensitive layer, making the development opening area cleaner and maintaining good copper surface adhesion stability. By further controlling the above-mentioned weight-average molecular weight and acid value, the risk of development residue, pattern edge defects, and electroplating solution penetration during VCP pattern electroplating is reduced, thereby further improving the electroplating reliability of the resist pattern. Specifically, the weight-average molecular weight of the alkali-soluble resin can be in the range of 80,000 g / mol, 90,000 g / mol, 100,000 g / mol, 110,000 g / mol, 120,000 g / mol, or any combination thereof; the acid value of the alkali-soluble resin can be in the range of 120 mg KOH / g, 140 mg KOH / g, 160 mg KOH / g, 180 mg KOH / g, 200 mg KOH / g, or any combination thereof.

[0052] In a second aspect, the present invention provides a photosensitive dry film comprising a support layer, a photosensitive layer and a protective layer disposed sequentially; wherein the photosensitive layer is formed by coating and drying the aforementioned photosensitive resin composition.

[0053] In a specific implementation of this invention, the above-mentioned photosensitive resin composition can be mixed and directly coated onto a support layer. After drying, a photosensitive layer is formed, and then a protective layer is laminated onto the photosensitive layer to finally obtain a photosensitive dry film. The support layer helps provide support for the photosensitive layer, facilitating the storage, transportation, cutting, and lamination of the photosensitive dry film. The protective layer helps protect the photosensitive layer before use, reducing the risk of contamination, scratches, or adhesion, thereby improving the stability and processing adaptability of the photosensitive dry film. In practical use, the protective layer can be removed, allowing the photosensitive layer to be laminated to the element to be processed, and the support layer can be removed, leaving the photosensitive layer covering the surface of the element to be processed. The element to be processed can be a conventional electronic device in the art, the support layer can be a PET film, and the protective layer can be a polyethylene (PE) film.

[0054] Because the photosensitive layer is formed using the aforementioned high-performance photosensitive resin composition, it possesses suitable absorbance per unit thickness of 385 nm, good alkaline developability, film-forming properties, and copper surface adhesion stability. Therefore, it facilitates the formation of resist patterns with appropriate curing degree, good resolution, clean development openings, and stable edges under LDI exposure conditions. Consequently, the photosensitive dry film is not only easy to laminate onto substrates such as copper-clad laminates, but also better suited for subsequent VCP pattern electroplating processes, reducing the risk of electroplating solution penetration, seepage, and copper delamination caused by insufficient resist pattern adhesion, poor edge sealing, or development residue.

[0055] In some embodiments, the thickness of the photosensitive layer is 20 μm to 50 μm. Controlling the thickness of the photosensitive layer helps reduce the problem of insufficient electroplating protection caused by an excessively thin photosensitive layer, and also helps reduce the problems of insufficient exposure, decreased resolution, or development residue caused by an excessively thick photosensitive layer, thereby further improving the edge integrity, adhesion stability, and electroplating resistance of the resist pattern. Specifically, the thickness of the photosensitive layer can be within the range of 20 μm, 25 μm, 30 μm, 40 μm, 50 μm, or any combination thereof.

[0056] In a third aspect, the present invention provides a printed circuit board, wherein the above-mentioned photosensitive dry film is used in the preparation process of the printed circuit board, and the preparation process of the printed circuit board includes LDI exposure, development and VCP pattern electroplating treatment.

[0057] Printed circuit boards are manufactured using the aforementioned photosensitive dry film, for example, according to the following steps. Specifically, firstly, the photosensitive layer of the photosensitive dry film is laminated onto the copper layer surface of a circuit-forming substrate such as a copper-clad laminate, so that the photosensitive layer adheres to the copper layer. Next, the copper-clad laminate with the laminated photosensitive layer is subjected to LDI exposure, so that the photosensitive layer forms a photocurable portion according to a predetermined circuit pattern. At this time, the photosensitive layer is subjected to LDI exposure through a support layer, and after exposure, it is left for at least 15 minutes to peel off the support layer.

[0058] Next, the area outside the photocured portion of the photosensitive layer is removed using a developer, exposing the copper layer area to be patterned for electroplating, while retaining the photocured portion as the resist pattern. Then, using the resist pattern as the electroplating resist layer, VCP pattern electroplating is performed on the developed copper-clad laminate, depositing the electroplated copper layer within the opening area defined by the resist pattern and bonding it to the exposed copper layer within that opening area. After the electroplated copper layer is formed, a tin plating layer can be formed on the surface of the electroplated copper layer.

[0059] After VCP pattern electroplating, the photocured portion of the photosensitive layer is peeled off or removed, i.e., the resist pattern is removed, exposing the copper layer not covered by the electroplated copper layer and / or electroplated tin layer. Subsequently, the exposed copper layer is etched, and the electroplated tin layer is removed after etching, thereby forming the desired conductor pattern and obtaining the printed circuit board.

[0060] Because the above preparation method uses the aforementioned high-performance photosensitive dry film, the photosensitive layer in this film has suitable absorbance per unit thickness of 385 nm, good alkaline developability, copper surface adhesion stability, and electroplating resistance. Therefore, it helps to form a resist pattern with good resolution, clean development openings, and stable edges after LDI exposure and development. During VCP pattern electroplating, the resist pattern can effectively prevent the electroplating solution from seeping in along the pattern edges and helps improve the bonding reliability between the electroplated copper layer and the original copper surface, thereby reducing plating penetration and copper delamination problems, and improving the pattern accuracy and electroplating reliability of the printed circuit board.

[0061] The present invention will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed by the present invention.

[0062] I. Raw Material Preparation

[0063] The specific parameters of the alkali-soluble resin used in the following examples and comparative examples are as follows:

[0064] Alkali-soluble resin A-1: ​​Prepared by solution polymerization, the monomers are methacrylic acid, methyl methacrylate, and butyl methacrylate in a mass ratio of 25:50:25; the weight-average molecular weight of A-1 is 97500 g / mol, and the acid value is 163 mg KOH / g resin. Specifically, the monomers corresponding to the alkali-soluble resin are mixed evenly according to the mass ratio (total 100 g). The monomers are mixed with 0.4 g of initiator AIBN, 100 g of butanone, and 5 g of ethanol to obtain a mixed solution, which is stirred and dissolved. Part of the mixed solution is added to a three-necked flask equipped with nitrogen protection and a reflux condenser using a peristaltic pump. The mixture is heated to 80°C in an oil bath and stirred for 1 h. The remaining mixed solution is then added dropwise, and all the mixed solution is added within 3 h. The reaction is continued at this temperature for 4 h, then the temperature is raised to 85°C, and 5 g of butanone solution containing 0.2 g of initiator is added. The reaction is then maintained at this temperature for 3 h to terminate the reaction and obtain the alkali-soluble resin.

[0065] Alkali-soluble resin A-2: Prepared by solution polymerization, the monomers being methacrylic acid, methyl methacrylate, butyl methacrylate, and styrene in a mass ratio of 25:50:15:10; A-2 has a weight-average molecular weight of 99000 g / mol and an acid value of 163 mg KOH / g resin. The preparation method of alkali-soluble resin A-2 is the same as above.

[0066] Alkali-soluble resin A-3: Prepared by solution polymerization, the monomers being methacrylic acid, methyl methacrylate, and butyl methacrylate in a mass ratio of 18:57:25; A-3 has a weight-average molecular weight of 98,000 g / mol and an acid value of 117 mg KOH / g resin. The preparation method of alkali-soluble resin A-3 is the same as above.

[0067] Alkali-soluble resin A-4: Prepared by solution polymerization, the monomers being methacrylic acid, methyl methacrylate, and 2-ethylhexyl methacrylate in a mass ratio of 25:50:25; the weight-average molecular weight of A-4 is 95000 g / mol, and the acid value is 163 mg KOH / g resin. The preparation method of alkali-soluble resin A-4 is the same as above.

[0068] The specific parameters of the photopolymerizable monomers used in the following examples and comparative examples are as follows:

[0069] Photopolymerizable monomer B-1: (8) nonylphenol acrylate ethoxylate, derived from strong electrons.

[0070] Photopolymerizable monomer B-2: (6) ethoxylated (12) propionic dimethacrylate, derived from strong electrons.

[0071] Photopolymerizable monomer B-3: (10) bisphenol A dimethacrylate ester, derived from Sartoma.

[0072] Photopolymerizable monomer B-4: (3) ethoxytrimethylolpropane triacrylate, derived from Sartoma.

[0073] It should be noted that the numbers in parentheses in the above-mentioned specific parameters of photopolymerizable monomers represent the average number of moles of ethylene oxide or propylene oxide structural units added in the corresponding monomer molecule.

[0074] The specific parameters of the photoinitiators used in the following examples and comparative examples are as follows:

[0075] Photoinitiator C-1: 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-diimidazole, derived from strong electrons.

[0076] Photoinitiator C-2: 4,4'-bis(diethylamino)benzophenone, derived from Aldrich.

[0077] Photoinitiator C-3: N-phenylglycine, derived from Aldrich.

[0078] II. Preparation of Photosensitive Resin Composition and Photosensitive Dry Film

[0079] According to the formulation shown in Table 1, alkali-soluble resin, photopolymerizable monomer, and photoinitiator were mixed in proportion, with an additional 0.05 parts by weight of diamond green and 0.45 parts by weight of leuco crystal violet added in this example and comparative example. Based on the solids content, appropriate amounts of butanone and ethanol were added to the alkali-soluble resin, and the mixture was stirred thoroughly until completely dissolved to prepare a resin composition solution with a solid content of 50%. The photosensitive resin composition solution was kept warm in a 30°C water bath and uniformly coated onto the surface of a PET film serving as a support layer using a coating machine. The PET film thickness was 15 μm. Subsequently, the coated sample was dried in a 95°C oven for 10 minutes to form a photosensitive layer with a thickness of 40 μm, which appeared green under yellow light. Next, a polyethylene film with a thickness of 20 μm was laminated onto the surface of the photosensitive layer as a protective layer, resulting in a photosensitive dry film comprising a support layer, a photosensitive layer, and a protective layer.

[0080] Table 1

[0081]

[0082] It should be noted that, in order to impart a suitable color to the photosensitive layer and facilitate observation of the coating state and the resist pattern after exposure and development, in this embodiment and comparative example, 0.05 parts by weight of diamond green and 0.45 parts by weight of leuco crystal violet were additionally added to each photosensitive resin composition. Both diamond green and leuco crystal violet were derived from Aldrich. The types and amounts of the above dyes remained the same in each embodiment and comparative example, and were not used as variables in the comparison between the embodiments and comparative examples.

[0083] Dyes are additives that can be added selectively according to actual needs, and are not essential components for achieving the technical effects of this invention. In other embodiments, the photosensitive resin composition may not include dyes, or at least one of malachite green, brilliant green, leuco crystal violet, or other commonly used dyes in the art may be used to replace the aforementioned dyes. Regardless of whether dyes are added, or whether the type and amount of dyes are adjusted, the absorbance per unit thickness of the resulting photosensitive layer at 385 nm should meet the range defined by this invention.

[0084] III. Sample Preparation and Testing Methods

[0085] 1. Applying a screen protector

[0086] The film was applied using a Changzhou Changyao Electronics CYL-M25 film applicator. The application pressure was 4 kg / cm². 2 The film application speed is 1m / min, and the film application temperature is 110℃.

[0087] 2. Exposure

[0088] After applying the film, let the sample stand for at least 15 minutes before exposing it using an LDI exposure machine. The LDI exposure machine model was Yingsu RS-RD-25, and the number of exposure grids was measured using a Stouffer 41-step exposure ruler, with the number of exposure grids controlled within the range of 17 to 23.

[0089] 3. Development

[0090] After exposure, allow the sample to stand for at least 15 minutes before development. The development temperature is 30℃, and the development pressure is 1.5 kg / cm². 2 The developer is a 1.0 wt% sodium carbonate aqueous solution, and the development time is 1.5 to 2.0 times the minimum development time; after development, wash with water and dry.

[0091] 4. Pattern electroplating

[0092] The electroplating solution used is a copper sulfate and stannous sulfate system from Zhengtianwei, with copper plating followed by tin plating. The specific process is as follows:

[0093] Acidic degreasing: 10% acidic degreasing solution concentration, 10 min time, 40℃ temperature; water washing for 2 min; micro-etching for 1 min, micro-etching solution is a mixture of 60 g / L sodium persulfate and 20 mL / L concentrated sulfuric acid; water washing for 1 min; acid leaching for 1 min, acid leaching solution is 10% sulfuric acid solution; copper electroplating: current density is 2 ASD, temperature is 22~27℃, time is 60 min; water washing for 1 min; acid leaching for 1 min, acid leaching solution is 10% sulfuric acid solution; tin electroplating: current density is 1 ASD, temperature is 20~25℃, time is 10 min.

[0094] 5. Remove film

[0095] The film was removed using an alkaline stripping method. The stripping solution was an aqueous NaOH solution. The stripping temperature was 50℃, and the pressure was 1.5 kg / cm². 2 The concentration of the stripping solution is 3-5 wt%, and the stripping time is 1.5-2.0 times the minimum stripping time; after stripping, wash with water and dry.

[0096] IV. Evaluation Methods

[0097] 1. Analysis and Evaluation

[0098] Exposure and development were performed using wiring patterns with equal line spacing and width ranging from 10 / 10μm to 70 / 70μm, with the line spacing and width increasing by 2.5μm each time. After washing and drying, the minimum width that allowed for the normal formation of cured resist lines was observed using a magnifying glass and recorded as the resolution value.

[0099] 2. Adhesion Evaluation

[0100] Exposure and development were performed using wiring patterns with equal line spacing and different line widths, where Line / Space = n / 400μm, and n ranged from 10 to 70μm, increasing by 2.5μm each time. After washing and drying, the minimum width that could form a complete cured resist line was observed using a magnifying glass and recorded as the adhesion value.

[0101] 3. Evaluation of electroplating resistance

[0102] After the samples undergo film application, exposure, development, pattern electroplating, and film removal, scanning electron microscopy is used to observe for any plating defects. The evaluation criteria are as follows:

[0103] ○: No plating penetration;

[0104] △: Slight plating penetration;

[0105] ×: Severe plating penetration.

[0106] 4. Ultraviolet absorption evaluation

[0107] The Agilent Cary 4000 UV-Vis spectrophotometer was used for testing, with a wavelength range of 200–800 nm. A PET film was used as the background sample. The protective film was removed before testing the sample, and the absorbance at 385 nm was recorded as A385.

[0108] The absorbance of each 1μm photosensitive layer is calculated using the following formula: Absorbance of each 1μm photosensitive layer = A385 / thickness of photosensitive layer.

[0109] The unit for the thickness of the photosensitive layer is μm.

[0110] 5. Evaluation of VCP copper plating

[0111] Extreme condition simulation tests were conducted. After development, the board was directly electroplated with copper without degreasing or micro-etching; the current density was 2 ASD, the temperature was 22~27℃, and the time was 30 minutes. After electroplating, the board was washed with water and dried, and then 3M tape was peeled off three times to observe whether there was any delamination of the electroplated copper.

[0112] The test results are shown in Table 2.

[0113] V. Test Results

[0114] Table 2

[0115]

[0116] VI. Results Analysis

[0117] As shown in Tables 1 and 2, compared to Comparative Examples 1-3, the photosensitive resin compositions of Examples 1-7 all include alkali-soluble resin, photopolymerizable monomers, and photoinitiators. Furthermore, the alkali-soluble resins used are all obtained by copolymerizing carboxyl-containing unsaturated monomers and acrylate monomers. Simultaneously, the absorbance of the photosensitive layer per 1 μm at 385 nm in Examples 1-7 is 0.005-0.030. Therefore, the electroplating resistance of Examples 1-7 shows no plating penetration, and the VCP copper plating does not delaminate. This indicates that by using the aforementioned alkali-soluble resin system and controlling the absorbance per unit thickness at 385 nm within the range of 0.005-0.030, it helps the photosensitive layer form a resist pattern with good resolution, adhesion, and electroplating resistance after LDI exposure, thereby improving its adaptability to VCP pattern electroplating and reducing the risk of copper plating delamination.

[0118] Comparative Example 1 used the same alkali-soluble resin A-1 as Examples 1-5, but the amount of 2,4,5-triarylimidazolium dimer photoinitiator C-1 was 3.90 parts by weight, and the amount of ketone photoinitiator C-2 was further increased to 0.45 parts by weight. Since both C-1 and C-2 can affect the light absorption of the photosensitive layer at 385 nm, the higher amount of photoinitiator increased the absorbance of the photosensitive layer per 1 μm at 385 nm in Comparative Example 1 to 0.035. Due to the excessively high absorbance per unit thickness in Comparative Example 1, the incident light tends to concentrate more on the surface of the photosensitive layer and be absorbed, resulting in uneven curing between the surface and bottom of the photosensitive layer, which may lead to insufficient curing of the photosensitive layer near the copper surface. Consequently, both the resolution and adhesion values ​​increased to 50 μm, indicating a decrease in resolution and adhesion performance, and severe plating penetration was observed in the electroplating resistance. Although no delamination occurred in the VCP copper plating evaluation of Comparative Example 1, its severe plating penetration indicates a significant decrease in the edge blocking ability and electroplating stability of the resist pattern. Therefore, when the absorbance per unit thickness of 385nm is too high, it can easily affect the curing uniformity of the photosensitive layer in the thickness direction, thereby reducing the resolution, adhesion, and electroplating resistance of the resist pattern.

[0119] Comparative Example 2 uses an alkali-soluble resin A-2 containing styrene structural units. Specifically, A-2 is obtained by copolymerizing methacrylic acid, methyl methacrylate, butyl methacrylate, and styrene in a mass ratio of 25:50:15:10. Compared to the alkali-soluble resin A-1 used in the examples, A-2 introduces styrene structural units and correspondingly reduces the proportion of butyl methacrylate, which tends to increase the rigidity and hydrophobicity of the resin film, while decreasing its flexibility and adaptability to the microstructure of the copper surface. Furthermore, in Comparative Example 2, the amount of photoinitiator C-1 is only 3.00 parts by weight, and the amount of photoinitiator C-2 is only 0.03 parts by weight. In particular, the amount of ketone photoinitiator C-2, which has a significant impact on the 385nm light response, is significantly low, resulting in insufficient absorption of 385nm ultraviolet light by the obtained photosensitive layer. Therefore, the absorbance of the photosensitive layer in Comparative Example 2 at 385nm is only 0.004 per 1μm.

[0120] Under the combined influence of alkali-soluble resin containing styrene structural units and excessively low absorbance per unit thickness, the photosensitive layer of Comparative Example 2 is prone to insufficient light response or incomplete curing during LDI exposure, which may affect the cleanliness of the developing aperture and the adhesion stability between the photosensitive layer and the copper surface. Consequently, Comparative Example 2 exhibits a resolution and adhesion of 50 μm, slight plating penetration, and delamination of the VCP copper plating. These results indicate that when styrene structural units are introduced into the alkali-soluble resin and the absorbance per unit thickness of 385 nm is too low, the exposure curing state, developing cleanliness, and copper surface adhesion stability of the photosensitive layer may all be adversely affected, leading to a decrease in the plating reliability of the resist pattern and increasing the risk of copper delamination during VCP pattern plating.

[0121] Comparative Example 3 and Example 3 are identical in type and amount of all components except for the alkali-soluble resin used. Both exhibit an absorbance of 0.022 per μm of photosensitive layer at 385 nm, an exposure energy of 60 mJ, and resolution and adhesion of 40 μm. Example 3 uses alkali-soluble resin A-1 without styrene structural units, while Comparative Example 3 uses alkali-soluble resin A-2 containing styrene structural units. Although the exposure response, resolution, and adhesion performance of Comparative Example 3 are comparable to those of Example 3, Comparative Example 3 shows slight plating penetration during electroplating, and delamination occurs in the VCP copper plating. These results indicate that even with the same absorbance per unit thickness at 385 nm, the introduction of styrene structural units into the alkali-soluble resin may reduce the flexibility of the photosensitive layer, its adaptability to the microstructure of the copper surface, and its interface stability, thereby reducing the electroplating reliability of the resist pattern and increasing the risk of copper delamination during VCP pattern electroplating.

[0122] Further analysis of Comparative Examples 2 and 3 reveals that both used alkali-soluble resin A-2 containing styrene structural units. In Comparative Example 2, the amounts of photoinitiators C-1 and C-2 were relatively low, resulting in an absorbance of only 0.004 per μm of photosensitive layer at 385 nm. This increased the exposure energy required to achieve 20 exposure cycles to 80 mJ, and improved both resolution and adhesion to 50 μm. In Comparative Example 3, by adjusting the amount of photoinitiator, the absorbance per μm of photosensitive layer at 385 nm was increased to 0.022, while the exposure energy decreased to 60 mJ, and both resolution and adhesion improved to 40 μm. These results demonstrate that controlling the absorbance per unit thickness at 385 nm within a suitable range helps improve the exposure response, resolution, and adhesion performance of the photosensitive layer.

[0123] However, although Comparative Example 3 achieved the same levels of absorbance per unit thickness, exposure energy, resolution, and adhesion as Example 3, its electroplating resistance still exhibited slight plating penetration, and VCP copper plating still delaminated. This further illustrates that simply controlling the absorbance per unit thickness to 385 nm is insufficient to guarantee the electroplating reliability of the photosensitive layer. It is also necessary to use an alkali-soluble resin system without styrene structural units to better improve the interface stability and electroplating resistance of the resist pattern during VCP pattern electroplating.

[0124] Furthermore, compared to Examples 4 and 5, Examples 1-3 all used alkali-soluble resin A-1, which was obtained by copolymerizing methacrylic acid, methyl methacrylate, and butyl methacrylate in a mass ratio of 25:50:25. Meanwhile, the absorbance per 1 μm of photosensitive layer at 385 nm in Examples 1-3 was 0.008, 0.015, and 0.022, respectively. The exposure energy of Examples 1-3 was 60-70 mJ, the resolution and adhesion were both 40 μm, and the electroplating resistance showed no plating penetration. Furthermore, the VCP copper plating did not delaminate. These results indicate that further using a preferred ternary copolymer alkali-soluble resin and controlling the absorbance per unit thickness at 385 nm within the range of 0.008-0.022 helps to further balance the exposure speed, thickness-direction curing state, resolution performance, and adhesion performance of the photosensitive layer, thereby obtaining superior overall performance.

[0125] In Example 4, the amount of photoinitiator C-1 was reduced to 3.00 parts by weight, and the amount of photoinitiator C-2 was reduced to 0.05 parts by weight. Due to the reduced amounts of photoinitiators C-1 and C-2, the absorption capacity of the photosensitive layer for 385nm ultraviolet light decreased accordingly, resulting in a decrease in the absorbance of the photosensitive layer per 1μm at 385nm to 0.005 in Example 4. Correspondingly, the exposure energy required to achieve the same exposure count in Example 4 increased to 75mJ, indicating a decrease in its response efficiency to the LDI exposure light source.

[0126] In Example 5, the amount of photoinitiator C-1 was increased to 3.90 parts by weight, and the amount of photoinitiator C-2 was increased to 0.38 parts by weight. Due to the increased amounts of photoinitiators C-1 and C-2, the absorption capacity of the photosensitive layer for 385nm ultraviolet light was correspondingly enhanced, resulting in an increase in absorbance per 1μm of photosensitive layer at 385nm to 0.030 in Example 5. Correspondingly, the exposure energy required to achieve the same exposure count in Example 5 was reduced to 50mJ, indicating an improved exposure response speed; however, the higher absorbance per unit thickness may cause more light energy to concentrate on the surface of the photosensitive layer, affecting the curing uniformity along the thickness direction of the photosensitive layer.

[0127] Although both Examples 4 and 5 exhibited no plating penetration and no delamination of VCP-plated copper, their resolution and adhesion were both 45 μm. The difference in Example 4 was primarily due to lower absorbance per unit thickness, leading to insufficient exposure response and requiring higher exposure energy to achieve the desired curing degree. Example 5, on the other hand, was mainly due to higher absorbance per unit thickness, which may have reduced curing uniformity between the surface and bottom of the photosensitive layer. These results indicate that further controlling the absorbance per unit thickness at 385 nm to 0.008–0.022 within the range of 0.005–0.030 can help improve the resolution and adhesion of the resist pattern.

[0128] Furthermore, in Examples 2, 6, and 7, except for the alkali-soluble resin, the types and amounts of other components are the same, and the absorbance of each 1 μm photosensitive layer at 385 nm is 0.015. The main difference lies in the alkali-soluble resin used. Example 2 uses alkali-soluble resin A-1, which is obtained by copolymerizing methacrylic acid, methyl methacrylate, and butyl methacrylate in a mass ratio of 25:50:25. Example 6 uses alkali-soluble resin A-3, which, although also obtained by copolymerizing methacrylic acid, methyl methacrylate, and butyl methacrylate, has a mass ratio of 18:57:25; at the same time, the acid value of A-3 is 117 mg KOH / g.

[0129] Because A-3 contains a relatively low proportion of methacrylic acid and a relatively high proportion of methyl methacrylate, and has a low acid value, the resin's alkaline developability and copper-surface interfacial interaction may be reduced, while the film rigidity may be relatively increased. Therefore, although Example 6 exhibits no plating penetration and no delamination of VCP-plated copper, its resolution and adhesion are both 45 μm. These results indicate that further controlling the mass ratio of methacrylic acid, methyl methacrylate, and butyl methacrylate, as well as the resin acid value, within a preferred range helps to further balance alkaline developability, film strength, flexibility, and copper-surface adhesion stability.

[0130] Example 7 uses alkali-soluble resin A-4, which is obtained by copolymerizing methacrylic acid, methyl methacrylate, and 2-ethylhexyl methacrylate in a mass ratio of 25:50:25. Specifically, 2-ethylhexyl methacrylate replaces butyl methacrylate in A-1 as the third comonomer. While 2-ethylhexyl methacrylate has relatively long and branched alkyl segments, which can improve film flexibility, it may also reduce film hardness, pattern retention, and dimensional stability in alkaline developing solutions.

[0131] Therefore, although Example 7 exhibited no plating penetration and no delamination of VCP-plated copper, its resolution and adhesion were both 45 μm. These results demonstrate that, within the range of carboxyl-containing unsaturated monomers and acrylate monomers defined in this invention, other acrylate monomers such as 2-ethylhexyl methacrylate can still meet the basic requirements for resolution, adhesion, and electroplating resistance. However, the preferred ternary copolymer system formed by methacrylic acid, methyl methacrylate, and butyl methacrylate is more conducive to balancing film strength, flexibility, alkali developability, pattern retention, and copper surface adhesion stability.

[0132] In summary, the test results of Examples 1-7 and Comparative Examples 1-3 show that the present invention, by using an alkali-soluble resin obtained by copolymerization of carboxyl-containing unsaturated monomers and acrylate monomers, and controlling the absorbance of the photosensitive resin composition at 385 nm per 1 μm of photosensitive layer to be 0.005-0.030, helps to form a resist pattern with good resolution, adhesion and electroplating resistance after LDI exposure, and improves the adaptability of the resist pattern to VCP pattern electroplating treatment, thereby reducing the risk of plating penetration and copper delamination.

[0133] Furthermore, by controlling the absorbance of the photosensitive resin composition at 385 nm per 1 μm of photosensitive layer to be 0.008~0.022, and using an alkali-soluble resin obtained by copolymerizing methacrylic acid, methyl methacrylate, and butyl methacrylate in a preferred mass ratio, it is helpful to further balance the exposure response speed, thickness direction curing uniformity, alkali developability, film strength, flexibility, and copper surface adhesion stability of the photosensitive layer. This further improves the resolution, adhesion, and electroplating resistance of the resist pattern, and enhances the bonding reliability between the electroplated copper layer and the original copper surface during the VCP pattern electroplating process.

[0134] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Those skilled in the art will recognize that the present invention can have various modifications and variations. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A photosensitive resin composition, characterized in that, The photosensitive resin composition includes an alkali-soluble resin, a photopolymerizable monomer, and a photoinitiator; The absorbance per unit thickness of the photosensitive resin composition under ultraviolet light at a wavelength of 385 nm is 0.005~0.030; wherein, the absorbance per unit thickness is the absorbance of a coating formed by the photosensitive resin composition with a thickness of 1 μm. The alkali-soluble resin is obtained by copolymerization of carboxyl-containing unsaturated monomers and acrylate monomers.

2. The photosensitive resin composition according to claim 1, characterized in that, The photosensitive resin composition has an absorbance of 0.008~0.022 per unit thickness under ultraviolet light with a wavelength of 385nm.

3. The photosensitive resin composition according to claim 1, characterized in that, The carboxyl-containing unsaturated monomers include at least one of acrylic acid, methacrylic acid, butenoic acid, maleic acid, maleic anhydride, and itaconic acid. And / or, the acrylate monomers include at least one of methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, amyl methacrylate, hexyl methacrylate, lauryl methacrylate, octadecyl methacrylate, hydroxymethyl methacrylate, hydroxyethyl methacrylate, ethyl N,N-dimethyl (meth)acrylate, ethyl N,N-diethyl (meth)acrylate, propyl N,N-dimethyl (meth)acrylate, and propyl N,N-diethyl (meth)acrylate.

4. The photosensitive resin composition according to claim 3, characterized in that, The carboxyl-containing unsaturated monomer includes at least one of acrylic acid and methacrylic acid; the acrylate monomer includes at least one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, and cyclohexyl methacrylate. Preferably, the alkali-soluble resin is obtained by copolymerization of the methacrylic acid, the methyl methacrylate, and the butyl methacrylate; More preferably, the mass ratio of the methacrylic acid to the methyl methacrylate is (20~30):(45~55); The mass ratio of methyl methacrylate to butyl methacrylate is (45~55):(20~30). The mass ratio of the methacrylic acid to the butyl methacrylate is (20~30):(20~30).

5. The photosensitive resin composition according to any one of claims 1 to 4, characterized in that, The photosensitive resin composition comprises, by weight, 40-70 parts of the alkali-soluble resin, 20-50 parts of the photopolymerizable monomer, and 3-10 parts of the photoinitiator.

6. The photosensitive resin composition according to claim 5, characterized in that, The photoinitiator includes at least one of 2,4,5-triarylimidazolium dimer compounds, ketone photoinitiators, N-phenylglycine, acridine compounds, and coumarin compounds; The 2,4,5-triarylimidazolium dimer compounds include at least one of 2,2'-di(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-diimidazole and (2,2',4-tris(2-chlorophenyl)-5-(3,4-dimethoxyphenyl)-4',5'-diphenyl-1,1'-diimidazole); the ketone photoinitiator includes at least one of 4,4'-bis(diethylamino)benzophenone, 4,4'-bis(dimethylamino)benzophenone, and 4,4'-dimethoxybenzophenone; the acridine compounds include at least one of 9-phenylacridine, 9-(p-methylphenyl)acridine, and 9-(m-methylphenyl)acridine; and the coumarin compounds include at least one of 7-diethylamino-4-methylcoumarin, 3-phenyl-7-aminocoumarin, and 3-heterocyclic-7-aminocoumarin. And / or, the photopolymerizable monomer includes at least one of nonylphenol acrylate, ethoxylated nonylphenol acrylate, ethoxylated propionylphenol acrylate, ethoxylated propionyl dimethacrylate, bisphenol A dimethacrylate, ethoxylated bisphenol A dimethacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propionyl trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, di-trimethylolpropane tetraacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate.

7. The photosensitive resin composition according to claim 6, characterized in that, The photoinitiator includes the 2,4,5-triarylimidazolium dimer compound, the ketone photoinitiator, and N-phenylglycine; Preferably, the mass ratio of the 2,4,5-triarylimidazolium dimer compound, the ketone photoinitiator, and the N-phenylglycine is (3.0~4.0):(0.05~0.4):(0.01~0.04).

8. The photosensitive resin composition according to claim 5, characterized in that, The photosensitive resin composition further comprises, by weight, 0.2 to 5.0 parts of additives and 100 to 200 parts of solvent; wherein the additives include at least one of adhesion promoters, plasticizers, dyes, fillers, flame retardants, stabilizers, leveling agents, peel accelerators, antioxidants, fragrances, imaging agents, and thermal crosslinking agents. And / or, the weight-average molecular weight of the alkali-soluble resin is 50,000 g / mol to 150,000 g / mol; Preferably, the weight-average molecular weight of the alkali-soluble resin is 80,000 g / mol to 120,000 g / mol; And / or, the acid value of the alkali-soluble resin is 100 mg KOH / g to 200 mg KOH / g; Preferably, the acid value of the alkali-soluble resin is 120 mg KOH / g to 200 mg KOH / g.

9. A photosensitive dry film, characterized in that, The photosensitive dry film comprises a support layer, a photosensitive layer, and a protective layer arranged sequentially; wherein the photosensitive layer is formed by coating and drying the photosensitive resin composition according to any one of claims 1 to 8; Preferably, the thickness of the photosensitive layer is 20μm to 50μm.

10. A printed circuit board, characterized in that, The printed circuit board is manufactured using the photosensitive dry film of claim 9, and the manufacturing process of the printed circuit board includes LDI exposure, development and VCP pattern electroplating.